PENINGKATAN KEMAMPUAN PENALARAN SISWA MELALUI MODEL PROBLEM BASED LEARNING (PBL) DITINJAU DARI KEMAMPUAN AKADEMIK SISWA DI SMA - Indra Drajat Sopwan (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2019)
The research was to analyze the improvement of students' reasoning students through the model Problem Based Learning (PBL) in terms of academic ability in high school. This research is a quasi experimental. This research was designed using a factorial design experiment. The study population was all students of class XI IPA at SMAN 1 Darma in the 2014/2015 school year as much as 5 classes. Sampling by using cluster random sampling technique. The research sample of grade XI IPA 1 and XI IPA 3 as an experimental class and XI IPA 2 as the control class. The collection of data with the test description, method of observation (assessment of performance capability of reasoning, observation sheets PBL, and self assessment) and documentation. Test the hypothesis by using parametric statistical tests in this case to test the hypothesis using the t test improvement was obtained p <0.05 is 0.044 <0.05, which means there is increasing students' reasoning skills and two-way ANOVA test to determine the application of PBL models include: (1 ) There are differences in reasoning abilities of students who apply models that do not apply the PBL and PBL models (p <0,05; 0,000 <0,05). (2) There is no difference in reasoning abilities of students based on academic ability (p> 0,05; 0,203> 0,05). (3) There is no interaction between the model PBL and academic skills with reasoning (p> 0,05; 0,981> 0,05).